Inmate Constitutional Claims and the Scienter Requirement - Ann Woolhandler; Michael Collins (Washington University Law Review, 2020)
Scholars have criticized requirements that inmates prove malice or deliberate indifference to establish constitutional claims against corrections officials. The Eighth Amendment currently requires convicted prisoners to show that a prison official acted “maliciously or sadistically” to establish an excessive force claim and with subjective “deliberate indifference” to establish a claim of unconstitutional prison conditions. Similar requirements can apply with respect to claims by pretrial detainees, whose claims are governed by substantive due process rather than the Eighth Amendment. Scienter critics have argued for use of an objective reasonableness standard for all inmate claims—both those brought by convicted prisoners and pretrial detainees. This Essay argues that the scienter requirements are more justified than critics claim. Critics argue that the Court has based its state-of-mind requirements on a mistaken notion that, for an action to constitute punishment, it must necessarily involve a purpose to chastise or deter. Intentions to chastise and deter, however, remain central to the concept of punishment, and reference to other purposes of punishment does not suggest dispensing with a culpable state-of-mind requirement in inmate suits against corrections officials. Scienter requirements, moreover, may be justified apart from notions of punishment, by the need to maintain order in prisons and to distinguish constitutional violations from ordinary torts. Finally, state-of-mind requirements do not pose the impenetrable barrier to liability that critics claim. This is particularly true in systemic conditions cases—the cases that have the most promise for improving the lives of inmates.
Keywords: Scienter; Eighth amendment; Unconstitutional prison conditions; Excessive force; Prison condition lawsuits; Objective reasonableness; Deliberate indifference